Hadis Misoginis Tentang Peran Domestik Perempuan: Telaah Kritis dalam Membangun Pemahaman yang Adil dan Setara - Adelia Putri; Muhajirin; Hedhri Nadhiran; Mugiono; Nurchalidin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This article examines a number of prophetic traditions (hadiths) that are commonly categorized as misogynistic, namely those perceived as degrading women or reflecting gender bias. Through an analytical–critical approach combined with contextual and historical interpretation, this study demonstrates that misogynistic understandings do not originate from Islamic teachings, but rather from patriarchal cultural constructions, mythologies of female creation found in Judeo–Christian traditions, and religious interpretations that overlook the moral and social contexts of the hadiths. The analysis explores several key narrations, including the command for wives to obey their husbands, the creation of women from a rib, women as the majority inhabitants of Hell, and the issue of female leadership. Findings indicate that these hadiths contain ethical messages, relational values, and principles of mutual responsibility rather than serving as instruments of discrimination. Reception analysis further reveals that literal readings detached from context often give rise to gender bias. In essence, Islam elevates the dignity of women, granting them access to education, social participation, and self-actualization. This article emphasizes the importance of interpreting hadith comprehensively—integrating historical analysis, maqāṣid al-sharī‘ah, and gender hermeneutics—so that Islamic teachings on justice, equality, and human dignity can be understood proportionally.